Enfleshed ecologies of entities and beings - Dolphijn, Rick; Deng, Zoénie; Dudeck, Stephan 1970-; Vagt, Christian; Ajvaseda, Jurij K. 1948-2013; Elfving, Taru; Esposito Yussif, Giovanna 1981-; Muñoz Alcántara, David; Xiaodong, Fu; Xiaohan, Han; You, Mi; OMFO 1966-; et al. (Onomatopee Projects, 2023)
Enfleshed: Ecologies of Entities and Beings brings together practitioners, thinkers, and artists from across Eurasia to collectively explore multispecies ecologies. The volume reflects anthrodecentric and embodied approaches to collaboration and knowledge production––processes that are always interwoven with a multitude of entities and actors. In this book, the contributions flow like a river across the Eurasian continent, branching out into all directions. The contributors engage in an exploration of experimental epistemic alliances, which operate as a way to learn and make new dialogic relations. The conflicts generated by ecological disaster, war, the global economy, identity politics, and the power structures of knowledge production and science here intertwine with shamanisms, rituals, magic, speculation, politics, and poetics. How do we imagine an active and implicated role of the human as one being among other beings? What might this entail, and what might this generate?
Keywords: Ökologie; Natur; Kunst; Mensch; Konflikt